Effects of Complex Carbohydrate from White Jack Bean (Canavalia ensiformis L. DC.) Flour after Autoclaving-Cooling Cycles on Short Chain Fatty Acids, Digesta Cholesterol Content and Bile Acid Binding in Hypercholesterolemic Rats - Rahmawati, Atina; Murdiati, Agnes; Marsono, Yustinus; Anggrahini, Sri (Pakistan Journal of Nutrition, 2018)
Background and Objective: Complex carbohydrate is a mixture of dietary fibre and starch present in food. The maximum complex carbohydrate content of white jack bean (Canavalia ensiformis) can be achieved by treating white jack bean with three autoclaving-cooling cycles. The objectives of this study were to evaluate the effects of complex carbohydrate from white jack bean following autoclaving-cooling on hypercholesterolemic rats and to assess its bile acid binding ability (in vitro). Methodology: Thirty Sprague-Dawley rats were divided into the following 6 groups: K1, a healthy control group; K2, a negative control group (hypercholesterol); K3, a positive control group (simvastatin); K4, a group administered a diet containing complex carbohydrate flour (5%), K5: a group administered a diet containing complex carbohydrate flour treated with autoclaving-cooling (5%) and K6, a group administered a diet containing complex carbohydrate flour treated with autoclaving-cooling (10%). The intervention lasted 4 weeks. The parameters observed were body weight, lipid profile, short-chain fatty acid (SCFA) profile, digesta cholesterol and bile acid binding ability (in vitro). Results: The hypercholesterolemic rats of the K6 group, which were fed a diet containing complex carbohydrate flour treated with autoclaving-cooling, exhibited maintained body weight and an improved lipid profile equivalent to those of the K3 positive control group (simvastatin). The rats of the K6 group could produce SCFAs with an acetic:propionic:butyric molar ratio of 50:39:11. The complex carbohydrate flour treated with autoclaving-cooling was able to bind 17.54% of the cholic acid and 32.43% of the deoxycholic acid. The K6 group was able to bind 100.36 mg/100 g digesta cholesterol. Conclusion: The K6 group achieved the best results in terms of maintaining the body weight and improving the lipid profile of hypercholesterolemic rats to levels equivalent to those of the K3 positive control group (simvastatin). The K6 group also exhibited an improved SCFA molar ratio with the ability to bind bile acids (in vitro) and digesta cholesterol.